Divestiture in the New Zealand Grocery Sector? An Analysis and Application of the Principles of Divestiture in the Context of the New Zealand Grocery Sector - Eccles, John (Victoria University of Wellington Law Review, 2025)
There is considerable concern about the state of competition in the New Zealand grocery sector. Recent responses from the Government have not helped to quell this. Many believe that only structural separation in the form of divestiture will restore competition to the grocery sector. This article examines the findings of the Commerce Commission’s market study of the grocery sector and the Government’s response to those findings. It then sets out the principles of divestiture as applied by New Zealand and United States courts. Finally, it applies these principles to the New Zealand grocery sector. Overall, it argues that courts must consider three key elements when analysing divestiture as an anti-competitive remedy: first, causation; secondly, the effect of the divestiture; and thirdly, the applicability of alternative remedies. Applying each of these elements to the grocery sector reveals that, whilst there would be some difficulty in implementation, the grocery sector is one where divestiture would likely be favoured by a court.